A dimensão da criatividade e do pensamento crítico no ensino de Ciências e Biologia - Zancheta, Maria Fernanda Castilho (Universidade Federal de São Carlos, 2025)
Creativity has long been scarcely associated with cognitive and emotional abilities, nor has it been strongly linked to the various fields of learning, including the sciences. Nowadays, creative thinking is associated with critical thinking, problem-solving, and decision-making, which justifies the importance and necessity of Science and Biology education in creating conditions for the development of critical-creative thinking. Although creativity is listed as a competency in the Brazilian National Common Curricular Base (BNCC), it is often hindered and remains little studied within the school context. A study was conducted with the purpose of analyzing the extent to which students’ creativity is expressed throughout the school years, comparing how middle school and high school students from a state school in the municipality of São Carlos (SP) solve problems creatively. A problem-situation type activity was applied and evaluated by judges based on pre-established categories from the Torrance and Wechsler Creativity Tests. The results revealed several qualitatively creative responses; however, quantitatively, high school students achieved better results. This situation leads us to question the education provided in the early and final years of middle school, the school curriculum, and the teaching and learning processes in Brazilian public education.
The dimension of creativity and critical thinking in Science and Biology education
Keywords: Criatividade; Ensino; Pensamento crítico-criativo; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM